Thermal self‐protection of zinc‐ion batteries enabled by smart hygroscopic hydrogel electrolytes - Yang, Peihua (2020)
Efficient thermal protection is essential to battery safety. Here, a self‐adaptive strategy is demonstrated to circumvent the thermal runaway of aqueous zinc‐ion batteries, by using a zinc chloride‐enriched hygroscopic hydrogel electrolyte. At high temperatures, water inside the hydrogel can quickly evaporate to dissipate the heat generated. Concurrently, excessive water evaporation causes a sudden drop in the ion diffusion of the hydrogel electrolyte, thereby effectively restricting the migration of ions and shutting down the battery. When the temperature lowers, the hydrogel absorbs water from the air and the battery recovers its function. The evaporation and regeneration of water in the hydrogel electrolytes are highly reversible, thus realizing intelligent and efficient thermal self‐protection of zinc‐ion batteries. By properly designing and engineering the hygroscopic hydrogel electrolytes, it is believed that other thermal self‐protective aqueous batteries with faster response can be abricated, which shows promise for a safe power supply in both consumable electronics and electric vehicles.